Agricultural extension policy, agricultural growth and poverty reduction in Indonesia - Rusliyadi, Muhamad; Bin Hj. Mohd. Jamil, Azaharaini; Maseleno, Andino; Tri Kumalasari, Ratna; Othman, Marini (International Journal of Engineering and Technology, 2019)
This paper presents an overview of agricultural growth, the extension policy and poverty reduction in Indonesia according to the most recent secondary data, as well as the data obtained from this study. It explains the growth in the agricultural sector in general, and the dynamics of agricultural extension at the national and regional levels in relation to poverty alleviation in rural development. In this paper, also the discussion focuses agricultural policy-based extension to enhance the performance of the agricultural sector in Indonesia and the link o Agricultural Extension with rural development by poverty reduction. The performance of the agricultural sector expressed as a growth rate has been relatively stagnant and unstable or volatile. The indicators of growth rate include produc-tion, growth, productivity rate and harvested area. The fluctuations of indicators tend to decline in terms of GDP growth and GDP share per total GDP. The performance of the agriculture sector during the period was unstable, depending on the circumstances at the time.Â Â